Chemical Composition of the Rectal Gland and Volatiles Released by Female Queensland Fruit Fly, Bactrocera tryoni (Diptera: Tephritidae). Issue 4 (30th May 2019) - El-Sayed, Ashraf M; Venkatesham, Uppala; Unelius, C Rikard; Sporle, Andrew; Pérez, Jeanneth; Taylor, Phillip W; Suckling, David M
Abstract: The composition of the rectal gland secretion and volatiles emitted by female Queensland fruit fly, Bactrocera tryoni was investigated. Esters were found to be the main compounds in the gland extracts and headspace, while amides were the minor compounds in the gland extracts and headspace. Ethyl dodecanoate, ethyl tetradecanoate, ethyl ( Z 9)-hexadecenoate and ethyl palmitate were the main esters in the gland extracts, while ethyl dodecanoate and ethyl tetradecanoate were the main esters in the headspace. Four amides ( N -(3-methylbutyl)acetamide), N -(2-methylbutyl)propanamide, N -(3-methylbutyl)propanamide, and N -(3-methylbutyl)-2-methylpropanamide were found in the gland extracts and the headspace. Among the amides, N -(3-methylbutyl)acetamide and N -(3-methylbutyl)propanamide were the main amides in the gland extracts and the headspace. Traces of three spiroacetals were found both in the gland extracts and in the headspace. ( E, E )-2, 8-Dimethyl-1, 7-dioxaspiro[5.5]undecane, ( E, E )-2-ethyl-8-methyl-1, 7-dioxaspiro[5.5]undecane, ( E, E )-2-propyl-8-methyl-1, 7-dioxaspiro[5.5]undecane. All compounds found in the headspace were present in the extract of the rectal gland suggesting that the rectal gland is the main source of the headspace volatiles, whose function remains to be elucidated. This is the first comprehensive chemical analysis of the rectal gland secretions and volatiles of female B. tryoni, and further laboratory and field bioassays are required to determine the function of compounds identified in this study. Discovery of the same amides previously identified in the male rectal gland in the female rectal gland raises questions about the pheromonal role previously suggested for these compounds.